2018
DOI: 10.22488/okstate.18.100504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Public Law 111-216 on Collegiate Flight Programs: Perceptions of Aviation Faculty and Flight Center Personnel

Abstract: In response to the 2009 Colgan 3407 airline crash and ensuing public concern, Public Law 111-216: The Airline Safety and Federal Aviation Administration Extension Act of 2010 was signed into law on August 1, 2010. This legislation mandated significant changes to the aviation and airline industries. Among these changes, an increase in pilot qualification standards was enforced for pilots seeking employment with US air carriers. This study explores the perceptions of aviation faculty members and flight center pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research by Depperschmidt (2013) found that collegiate aviation training institutions are concerned with increased program and training cost as a result of PL 111-216. Similarly, Depperschmidt, Bliss, and Casebolt (2015) discovered that as a result of the new legislation, collegiate flight students will begin to pursue flight careers (non-US airline or corporate aviation) that are not directly impacted by PL 111-216.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Research by Depperschmidt (2013) found that collegiate aviation training institutions are concerned with increased program and training cost as a result of PL 111-216. Similarly, Depperschmidt, Bliss, and Casebolt (2015) discovered that as a result of the new legislation, collegiate flight students will begin to pursue flight careers (non-US airline or corporate aviation) that are not directly impacted by PL 111-216.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Review of the Literature All airline accidents result in increased scrutiny from the flying public, media, Department of Transportation, Federal Aviation Administration, and Congress, among others (Depperschmidt, Bliss, & Casebolt, 2015). During the last decade, three high-profile accidents occurred involving Part 121 air carrier operations at regional airlines: Pinnacle Airlines Flight 3701 (NTSB, 2007a), Comair Flight 5191 (NTSB, 2007b), and most notably Colgan Air Flight 3407 (NTSB, 2010) that resulted in loss of life of passengers, crew, and persons on the ground.…”
Section: Research Questionmentioning
confidence: 99%